Guidelines for laboratory work on the topic "Clustering Using SAP Predictive Analytics" - Yangolenko, Olga; Ivaschenko, Oksana; Melnyk, Karina; Yershova, Svetlana; Lutenko, Irina (Національний технічний університет "Харківський політехнічний інститут", 2024)
Aim: To fulfil clustering using SAP Predictive Analytics tool. Tools/ Apparatus: SAP Predictive Analytics.
Keywords: guidelines; laboratory work; clustering; SAP Predictive Analytics; clustering module; importing the data